CORRELATION BETWEEN LOCUS OF CONTROL WITH STRESS CARE OF NURSES IN HOSPITAL AT SOEBANDI HOSPITAL JEMBER - Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan; Afrize Rosalia (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2020)
Nurses are health workers who have an important role in the hospital. Nurses areprofessionals who have both positive and negative impacts. One of the negative impactsexperienced by nurses is the work stress of nurses. Nurse work stress is a situation wherenurses experience pressure caused by many tasks and jobs that cannot be fulfilled. Inaddition to the high workload, locus of control is also one of the factors that influencework stress on nurses. This study aimed to analyze the relationship between locus ofcontrol with nurses working stress in patients at dr. Soebandi Jember hospital. Thisstudy uses a correlational research design with a cross-sectional approach. A total of71 respondents used a purposive sampling approach using the locus of control scaleand OSI-R (Occupational Stress Inventory-Revised Edition). The statistical test usedis Spearman. The results are based on the Kendall Tau statistical test with a p-valueof 0.032 and a value of r = -0.249, which means that the relationship between locus ofcontrol and occupational nurses’ work stress has a negative correlation direction witha weak correlation strength. A negative correlation shows that the higher the locusof control in nurses, the lower the work stress experienced by nurses. A high locus ofcontrol on nurses has a positive impact on the quality of work of nurses, especially inmaintaining the emotional care of a nurse in carrying out professional tasks. Thereforethe hospital should be able to provide health education programs about the importanceof locus of control and work stress on nurses because it can affect the quality of nursingcare provided to patients.